Clinician factors related to the delivery of psychotherapy for autistic youth and youth with attention-deficit hyperactivity disorder. (February 2023) - Roudbarani, Flora; Tablon Modica, Paula; Maddox, Brenna B; Bohr, Yvonne; Weiss, Jonathan A
Autistic children and adolescents are more likely than non-autistic youth to experience mental health problems, such as anxiety or depression, but less likely to receive psychotherapy to address these concerns. Recent research indicates that clinician factors, such as knowledge, attitudes, confidence and beliefs, can impact their decisions to provide care, though this work has primarily focused on adults or within the context of one kind of treatment (cognitive behaviour therapy). The current study examined psychological predictors (e.g. attitudes and confidence) of clinicians' intention to deliver psychotherapy to autistic youth and those with attention-deficit hyperactivity disorder. Participants included 611 clinicians across publicly funded agencies in Ontario, Canada. Multiple mediation analyses revealed that clinician knowledge on mental health-related topics (e.g. core symptoms, developing treatment plans and identifying progress towards treatment goals) was associated with intention to treat autistic clients or clients with attention-deficit hyperactivity disorder, and normative pressures and attitudes partially mediated this association. Clinicians felt less likely to treat autistic clients than clients with attention-deficit hyperactivity disorder, partly because of differences in attitudes, normative pressures and knowledge. This research suggests that targeted training around autism and mental health care may be a useful initiative for agency staff. Lay abstract: Autistic children and youth often experience mental health problems, such as anxiety, depression and behavioural challenges. Although there are therapy programmes that have been found helpful in reducing these issues, such as cognitive behaviour therapy, autistic children often struggle to receive adequate mental health care. Clinicians' knowledge, attitudes, confidence and beliefs about treating mental health problems in autistic people may be related to their choices in providing psychotherapy. Across Ontario, Canada, 611 mental health clinicians, working in publicly funded agencies, completed an online survey about their experiences and opinions on delivering therapy for autistic clients compared to those with attention-deficit hyperactivity disorder. Clinician knowledge was associated with their intention to treat autistic clients or clients with attention-deficit hyperactivity disorder, partly because of their attitudes and the social pressures or values they felt. Clinicians reported feeling less intent on providing therapy to autistic youth compared to youth with attention-deficit hyperactivity disorder because of differences in their attitudes, social pressures and knowledge. This research can inform the training and educational initiatives for mental health practitioners.